Perancangan Aplikasi Quality Information Notice Berbasis Website - Rosi Kusuma Serli; Mulia Rahmayu; Tatang Permana (Universitas PGRI Kanjuruhan Malang, 2020)
Warehouse is an important component of modern supply chains. Warehouses can be described as part of a logistics system of a company that serves to store products and provide information about the status and condition of materials or inventories stored in the warehouse. In this case, especially for PT. YCH INDONESIA creates unfeasible product condition report when inbound process with document or system and product finding is broken on stock of locator to its biggest customer that is PT. Frisian Flag Indonesia called QIN (Quality Information Notice). At present, to save inappropriate product findings, PT YCH Indonesia uses physical files stored in an ordner. In this way the possibility of loss of documents or files becomes larger. From these problems raises the idea to create a system of QIN (Quality Information Notice) application that serves to store data findings that are not appropriate product when the inbound process and the findings of broken products in the locator. The method used is waterfall method using web-based programming language in order to be accessible by users from various warehouses branch. Supported with the availability of local internet network (intranet) within the company.